Development of OCIPSE Learning Model to Increase Students’ Scientific Creativity in Natural Science Learning - Rizqi; Prabowo; Tjandra Kirana (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2020)
This Research & Development (R & D) has the main goal to develop and produce OCIPSE learning model. The main product of this research is the OCIPSE learning model with five phases, they are 1) Orient and organize the students for study; 2) Collaborative Investigation; 3) Presentation and discussion; 4) Strengthening of scientific creativity; and 5) Evaluate and provide recognition. The OCIPSE learning model’ quality data is obtained through an expert validation process by using the OCIPSE learning model Qualification Assessment Instrument. The OCIPSE learning model quality analysis used an average validity score, single measures ICC, and Cronbach's coefficient alpha. The result of the research shows OCIPSE learning model with average content validity (3.69), construct validity (3.69), with the validity of each aspect statistically in (rα = .92) and reliability in (α = .87). The results of this study indicate that the developed OCIPSE learning model was declared qualified by experts. The research implication is that a qualified OCIPSE learning model can be used to enhance the scientific creativity of junior high school students in natural science learning.